Cognitive and health-related outcomes after exposure to early malnutrition: The Leiden longitudinal study of international adoptees. (January 2015) - Schoenmaker, Christie; Juffer, Femmie; van IJzendoorn, Marinus H.; van den Dries, Linda; Linting, Mariëlle; van der Voort, Anja; Bakermans-Kranenburg, Marian J.
Abstract: Background: We followed 190 internationally adopted children from infancy to young adulthood to examine the long-term consequences of early malnutrition on cognitive and health-related outcomes. Method: We measured birth weight and physical condition in infancy, IQ and somatic problems in middle childhood, adolescence and young adulthood; in young adulthood, socioeconomic success was also assessed. Results: Early malnutrition negatively affected IQ in middle childhood and to a lesser extent IQ in young adulthood, but a negative effect on socioeconomic success was absent. Higher levels of early malnutrition predicted more somatic problems in middle childhood. Conclusions: Variation in early malnutrition explains differences in cognitive and health-related outcomes, with early malnutrition predicting lower IQs in middle childhood and in young adulthood. Early malnutrition did however not negatively affect the young adult's socioeconomic success, indicating that early malnutrition may be compensated by later experiences. Highlights: Early malnutrition negatively affected IQ in middle childhood and to a lesser extent IQ in young adulthood. A negative effect of early malnutrition on socioeconomic success in young adulthood was absent. Early malnutrition may be compensated by later experiences, and its consequences may not extend to socioeconomic success later in life.